The Effect of Work-Life Balance on Employee Performance - Dede, Dede Sulaeman; Farhan, Akhmad; Winanti (Journal of E-business and Management Science, 2024)
There are still many companies that do not pay attention to the importance of work-life to improve employee performance, which has an impact on many jobs that are not completed on time, irresponsible employees and accumulated work. Involving employees in various company activities is able to foster a sense of responsibility. This study aims to find out whether there is an effect of work-life balance on employee performance. This study uses a quantitative approach. The sample of this study uses a nonprobability sampling technique with purposive sampling, the sample of this study is 77 people. Data collection uses a questionnaire which is then processed by the analysis method of validity and reliability test, correlation coefficient, determination coefficient and t-count test (partial test). The results of this study show that work-life balance has a positive effect on employee performance, work-life balance and employee performance have a positive relationship but the degree of relationship is low, which is only 5.6%.